2016
DOI: 10.1007/s11259-016-9671-8
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte maturation, embryo development and gene expression following two different methods of bovine cumulus-oocyte complexes vitrification

Abstract: Expression of oocyte maturation genes was affected by vitrification procedure and conditions. Using EG alone for vitrification of bovine immature COCs, resulted in higher expression of GDF9, BMP15 and production of more in vitro matured and cleaved oocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 43 publications
1
17
0
1
Order By: Relevance
“…We have not detected differences in the amount and the integrity of the total RNA in intact and vitrified/thawed groups of human ovarian tissue samples (data not shown). However, it has been previously shown that there is a statistically significant difference in transcript abundance in cells before and after vitrification [23][24][25]. Therefore, distortion of results can occur in the following cases: normalization to the total RNA or normalization to the mRNA of nonrepresentative reference gene.…”
Section: Discussionmentioning
confidence: 99%
“…We have not detected differences in the amount and the integrity of the total RNA in intact and vitrified/thawed groups of human ovarian tissue samples (data not shown). However, it has been previously shown that there is a statistically significant difference in transcript abundance in cells before and after vitrification [23][24][25]. Therefore, distortion of results can occur in the following cases: normalization to the total RNA or normalization to the mRNA of nonrepresentative reference gene.…”
Section: Discussionmentioning
confidence: 99%
“…Oocytes were loaded onto the tip of Cryotop (Kitazato Supply Co., Tokyo, Japan) in a small volume of vitrification solution and plugged into liquid nitrogen immediately. Warming of vitrified oocytes was done by immersing the Cryotop tip directly in a 37ºC warming solution composed of HM and 1 M sucrose for 1 min, followed by treatment with HM supplemented with 0.5 M for 3 min (15). Afterward, the retrieved oocytes were washed and transferred to HM until the next procedure.…”
Section: Experiments 2: Effects Of Niacin Addition In Ivm Medium On Crmentioning
confidence: 99%
“…Frozen semen which previously tested in the laboratory for IVF was used for fertilization. Motile spermatozoa from frozen/thawed semen were obtained using the swim-up method and were then added to wells containing oocytes at a final concentration of 10 6 spermatozoa ml−1 (12). Oocytes and spermatozoa were co-incubated at 38.5 • C for 18 h in 5% CO 2 .…”
Section: In Vitro Fertilizationmentioning
confidence: 99%
“…Communication between the oocyte and its surrounding cumulus cells is an important event for development of a competent oocyte (12). Growth differentiation factor (GDF9) and steroidogenic acute regulatory (StAR) proteins play a major role in oocyte developmental competence (13,14).…”
Section: Introductionmentioning
confidence: 99%